2016
DOI: 10.1002/ajmg.a.37670
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing reveals de novo pathogenic variants in KAT6A as a cause of a neurodevelopmental disorder

Abstract: Neurodevelopmental disorders (NDD) are common, with 1-3% of general population being affected, but the etiology is unknown in most individuals. Clinical whole-exome sequencing (WES) has proven to be a powerful tool for the identification of pathogenic variants leading to Mendelian disorders, among which NDD represent a significant percentage. Performing WES with a trio-approach has proven to be extremely effective in identifying de novo pathogenic variants as a common cause of NDD. Here we report six unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 44 publications
5
41
1
1
Order By: Relevance
“…Since 2015, around 80 cases of syndromic intellectual disability due to mutations at the KAT6A gene have been described in the literature, delineating a new syndrome with variable presentation ( Table 2 and Fig. 3) [4][5][6][7][8][9][10][11][12][13][14][15]. Here, we present 5 patients with de novo variants at KAT6A, four 'late truncating' and one missense variant, and we describe their clinical presentations, adding further clinical and molecular delineation to the KAT6A syndrome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since 2015, around 80 cases of syndromic intellectual disability due to mutations at the KAT6A gene have been described in the literature, delineating a new syndrome with variable presentation ( Table 2 and Fig. 3) [4][5][6][7][8][9][10][11][12][13][14][15]. Here, we present 5 patients with de novo variants at KAT6A, four 'late truncating' and one missense variant, and we describe their clinical presentations, adding further clinical and molecular delineation to the KAT6A syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…32; MIM # 616268). To date, a total of 79 patients have been reported [4][5][6][7][8][9][10][11][12][13][14][15]. All of them present with developmental delay (DD) or intellectual disability (ID) with speech delay.…”
mentioning
confidence: 99%
“…In this regard, KAT6A , the gene whose promoter has the second top-binding site by ChIP, was down-regulated in our transcriptome analysis (table S3). Interestingly, mutations in KAT6A were recently identified in patients presenting with neurodevelopmental disorders (47). Lower KAT6A expression may contribute to the intellectual disabilities observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…With great interest we have read the article by Millan et al [] describing six patients with pathogenic de novo variants in KAT6A . The patients shared a common phenotype of moderate to severe neurodevelopmental delay, severe speech delay, hypotonia, and a characteristic face.…”
Section: Frequently Reported Clinical Characteristics In Patients Witmentioning
confidence: 99%
“…PSIS belongs to the spectrum of midline brain abnormalities and is often associated with other extra‐pituitary midline malformations (Reynaud et al, ). Thus, far 17 patients with dominantly acting mutations in KAT6A have been described, and in all affected individuals the phenotype consisted of neurodevelopmental and speech delay, and a typical facial morphology (Arboleda et al, ; Millan et al, ; Tham et al, ). Brain MRI studies were reported in 16 of these children, and demonstrated subtle midline brain abnormalities in three: one had a missing olfactory bulb (Millan et al, ), and two had a cavum of the septum pellucidum (Tham et al, ).…”
Section: Frequently Reported Clinical Characteristics In Patients Witmentioning
confidence: 99%